Endoscopic Anatomic Study Via Grinding Partial Petrous Ridge to the Middle Fossa in Retromastoid Keyhole Approach. Issue 4 (June 2018) - Tang, Can; Pang, Lujun; Zhang, Hengzhu; Yan, Zhengcun; Wang, Xiaodong; Dong, Lun; She, Lei; Wang, Xingdong; Wei, Min
Abstract : Objective: This study aimed to observe the range of exposure, indications, and feasibility of the retromastoid keyhole approach via grinding partial petrous ridge to the middle fossa. Methods: Simulated endoscopic surgeries via grinding suprameatal tubercle and petrous ridge to expose the middle fossa in retromastoid keyhole approach were performed on 8 adult cadaver heads (16 sides) fixed by formalin. The maximum exposure range in endoscope was observed. The boundaries of Parkinson triangle and the anatomic structures contained by Meckel cave and cavernous sinus (CS) lateral wall were revealed. The distances from midpoint of sigmoid sinus posterior border to every important anatomic structures in the middle fossa and the length of all sides of Parkinson triangle were measured. Results: By using endoscope, the exposure of the cerebellopontine angle, ventrolateral brainstem, incisure of tentorium, petroclival region, and CS lateral wall were satisfactory. Many important anatomic structures in middle fossa were exposed well. The distances from midpoint of posterior border of sigmoid sinus to suprameatal tubercle, trigeminal semilunar ganglion, posterior curve segment of internal carotid artery were 34.42 ± 2.14, 54.52 ± 2.87, and 65.15 ± 3.13 mm. The lengths of all sides of Parkinson triangle were 18.97 ± 2.93, 16.23 ± 2.02, and 8.04 ± 2.34 mm. Conclusion: The retromastoid keyhole approach via grinding partial petrous ridge to the middle fossa by using endoscope can increase the exposure of middle fossa effectively, which is proper for most lesions in posterior cranial fossa while some parts extend to middle fossa.